Direct and Indirect DNP NMR Uncovers the Interplay of Surfactants with Their Mesoporous Host Material - Döller, Sonja C.; Brodrecht, Martin; Gutmann, Torsten; Hoffmann, Markus; Buntkowsky, Gerd (The Journal of Physical Chemistry C)
Two different mesoporous silica materials (SBA-15 and MCM 41) were impregnated with four different, commercially available surfactants, namely, E5, PEG 200, C10E6, and Triton X-100. Differential scanning calorimetry was employed to confirm the confinement of the surfactants in the pores of their host materials. Dynamic nuclear polarization enhanced solid state 13C magic angle spinning (MAS) nuclear magnetic resonance (NMR) spectra were recorded for these materials, showing that both the direct as well as the indirect polarization transfer pathways are active for the carbons of the polyethylene glycol moieties of the surfactants. The presence of the indirect polarization pathway implies the presence of molecular motion with correlation times faster than the inverse Larmor frequency of the observed signals. The intensities of the signals were determined, and an approach based on relative intensities was employed to ensure comparability throughout the samples. From these data, the interactions of the surfactants with the pore walls could be determined. Additionally, a model describing the surfactants’ arrangement in the pores was developed. It was concluded that all carbons of the hydrophilic surfactants, E5 and PEG 200, interact with the silica walls in a similar fashion, leading to similar polarization transfer pathway patterns for all observed signals. For the amphiphilic surfactants C10E6 and Triton X-100, the terminal hydroxyl group mediates the majority of the interactions with the pore walls and the polarizing agent. Two different mesoporous silica materials (SBA-15 and MCM 41) were impregnated with four different, commercially available surfactants, namely, E5, PEG 200, C10E6, and Triton X-100. Differential scanning calorimetry was employed to confirm the confinement of the surfactants in the pores of their host materials. Dynamic nuclear polarization enhanced solid state 13C magic angle spinning (MAS) nuclear magnetic resonance (NMR) spectra were recorded for these materials, showing that both the direct as well as the indirect polarization transfer pathways are active for the carbons of the polyethylene glycol moieties of the surfactants. The presence of the indirect polarization pathway implies the presence of molecular motion with correlation times faster than the inverse Larmor frequency of the observed signals. The intensities of the signals were determined, and an approach based on relative intensities was employed to ensure comparability throughout the samples. From these data, the interactions of the surfactants with the pore walls could be determined. Additionally, a model describing the surfactants’ arrangement in the pores was developed. It was concluded that all carbons of the hydrophilic surfactants, E5 and PEG 200, interact with the silica walls in a similar fashion, leading to similar polarization transfer pathway patterns for all observed signals. For the amphiphilic surfactants C10E6 and Triton X-100, the terminal hydroxyl group mediates the majority of the interactions with the pore walls and the polarizing agent.

Higher rank quantum-classical correspondence - Hilgert, Joachim; Weich, Tobias; Wolf, Lasse Lennart (Analysis & PDE)
For a compact Riemannian locally symmetric space $Γ\backslash G/K$ of arbitrary rank we determine the location of certain Ruelle-Taylor resonances for the Weyl chamber action. We provide a Weyl-lower bound on an appropriate counting function for the Ruelle-Taylor resonances and establish a spectral gap which is uniform in $Γ$ if $G/K$ is irreducible of higher rank. This is achieved by proving a quantum-classical correspondence, i.e. a 1:1-correspondence between horocyclically invariant Ruelle-Taylor resonant states and joint eigenfunctions of the algebra of invariant differential operators on $G/K$.

Meromorphic Continuation of Weighted Zeta Functions on Open Hyperbolic Systems - Schütte, Philipp; Weich, Tobias; Barkhofen, Sonja (Communications in Mathematical Physics)
In this article we prove meromorphic continuation of weighted zeta functions in the framework of open hyperbolic systems by using the meromorphically continued restricted resolvent of Dyatlov and Guillarmou (2016). We obtain a residue formula proving equality between residues of weighted zetas and invariant Ruelle distributions. We combine this equality with results of Guillarmou, Hilgert and Weich (2021) in order to relate the residues to Patterson-Sullivan distributions. Finally we provide proof-of-principle results concerning the numerical calculation of invariant Ruelle distributions for 3-disc scattering systems.

Explaining Face Recognition Through SHAP-Based Pixel-Level Face Image Quality Assessment - Biagi, Clara; Rethfeld, Louis; Kuijper, Arjan; Terhörst, Philipp (2023 IEEE International Joint Conference on Biometrics (IJCB))

A novel indexing algorithm for latent palmprints leveraging minutiae and orientation field - Khodadoust, Javad; Monroy, Raúl; Medina-Pérez, Miguel Angel; Loyola-González, Octavio; Kusakunniran, Worapan; Boller, André; Terhörst, Philipp (Intelligent Systems with Applications)

An EPR Study on Highly Stable Nitroxyl-Nitroxyl Biradicals for Dynamic Nuclear Polarization Applications at High Magnetic Fields - Asanbaeva, Nargiz B.; Dobrynin, Sergey A.; Morozov, Denis A.; Haro-Mares, Nadia; Gutmann, Torsten; Buntkowsky, Gerd; Bagryanskaya, Elena G. (Molecules)

Datenqualitätssicherung im Forschungsprozess am Beispiel von Zugversuchen - Müller, Laura; Wawer, Max Leo; Heimes, Norman; Uhe, Johanna; Koepler, Oliver; Auer, Sören; Lachmayer, Roland; Mozgova, Iryna (DS 125: Proceedings of the 34th Symposium Design for X (DFX2023))
Progressive digitization throughout the entire product data life cycle requires a more sensitive handling and understanding of data within engineering processes. Regarding engineering research data, the aim is to implement the FAIR data principles (Findable, Accessible, Interoperable, Reusable) to guarantee the post-usability of research data. To ensure the quality of data throughout the entire research process a methodical approach had been developed. Based on the quality categories Intrinsic, Representative, Contextual and Available, the related quality dimensions are considered differentiated along the research data life cycle and presented in a concept. As a use case, this concept is carried out on a tensile test with documentation of results in a research data management system.

Teleoperation of an Industrial Robot using Public Networks and 5G SA Campus Networks - Rohde, Jannik; Meyer, Olga; Duc, Quy Luu; Jürgenhake, Christoph; Sankal, Talib; Dumitrescu, Roman; Schmitt, Robert H. (2022 Sixth IEEE International Conference on Robotic Computing (IRC))

Digitalization and Sustainability in Strategic Management: Research Agenda toward Dual Transformation - Kurpick, Christian; Dumitrescu, Roman; Falkowski, Tommy; Fechtelpeter, Christian; Kühn, Arno (2022 IEEE 28th International Conference on Engineering, Technology and Innovation (ICE/ITMC) & 31st International Association For Management of Technology (IAMOT) Joint Conference)

Methode zur Simulation des temperaturabhängigen Crashverhaltens von strukturellen Klebverbindungen - Striewe, Marius; Teutenberg, Dominik; Hein, David; Meschut, Gerson; Schmelzle, Lars; Mergheim, Julia; Possart, Gunnar (Klebtechnische Doktorandenseminare 2020 - 2022)

Rechnergestützte Versagensanalyse geklebter Verbindungen - Chudalla, Nick; Meschut, Gerson; Teutenberg, Dominik; Schneider, Miriam; Smart, Dominic (adhäsion KLEBEN & DICHTEN)

Methodenentwicklung zur Prognose des Crashverhaltens von widerstandspunktgeschweißten 3-Stahlblechverbindungen - Olfert, Viktoria; Schuster, Lilia; Bähr, Philipp; Hein, David; Meschut, Gerson; Sommer, Silke
Die aktuellen politischen und wirtschaftlichen Rahmenbedingungen zur Reduzierung der CO2-Emissionen sowie der Trend zur flächendeckenden Elektromobilität führen zu einer Vielzahl an neuen Herausforderungen für die Auslegung zukünftiger Fahrzeugkonzepte. Eine besondere Herausforderung ist das durch die Batterie ins Fahrzeug eingebrachte Zusatzgewicht. Hierdurch ergibt sich ein Konflikt zu der bestehenden Kundenerwartung nach einer hohen Reichweite. Durch den umfangreichen Einsatz von höchstfesten Stählen in dünnen Blechdicken im Karosseriebau soll die Reduzierung des Gesamtfahrzeuggewichts vorangetrieben werden. Vor allem im stahlintensiven Leichtbau ist das Widerstandspunktschweißen aufgrund des hohen Automatisierungsgrads, der Prozesssicherheit und der damit verbundenen Wirtschaftlichkeit das dominierende Fügeverfahren. Um Begrenzungen des Bauraums der Karosserie zu begegnen und um den Materialeinsatz im Leichtbau möglichst effizient zu gestalten, werden mehrschnittige Punktschweißverbindungen eingesetzt. Hieraus ergeben sich neue Herausforderungen für die Vorhersage des Trag- und Versagensverhaltens unter Crashbelastung. Dieser Beitrag stellt eine systematische Charakterisierung von 3-Blechverbindungen zur Auffindung von formelmäßigen, empirischen Zusammenhängen zwischen der Festigkeit der Verbindung und den Einflussgrößen vor. Nach der Identifikation geeigneter Einflussgrößen, wie zum Beispiel Blechfestigkeit, Blechanordnung, Blechdickenkombination sowie Belastungsart und Lasteinleitung, auf das Trag- und Versagensverhalten, werden numerische Simulationen durchgeführt, um Ursachen für auftretende Phänomene aus den experimentellen Ergebnissen aufzuklären. Weiterhin wird untersucht, inwieweit das Verhalten von 2-Blechverbindungen auf 3-Blechverbindungen übertragbar ist. Die gefundenen Zusammenhänge sollen schnelle und kostengünstige Abschätzungen über die Festigkeit von 3-Blechbverbindungen ermöglichen. Darüber hinaus werden Ersatzmodelle für die Crashsimulation von 3-Blechverbindungen entwickelt, die recheneffizient für die Sicherheitsbewertung von großen, geschweißten Bauteilen eingesetzt werden können. Dabei sollen insbesondere die Einflüsse des Lastangriffs an jeweils einer oder beiden Fügebenen auf die Festigkeit und Energieabsorption unter verschiedenen Belastungen wie Zug, Scherung sowie Biegung abbildbar sein.

Extracting perfect GHZ states from imperfect weighted graph states via entanglement concentration - Frantzeskakis, Rafail; Liu, Chenxu; Raissi, Zahra; Barnes, Edwin; Economou, Sophia E. (Physical Review Research)

Die Stimmen der Eroberten bei Ermoldus Nigellus. Eine Mahnung an Ludwig den Frommen und Pippin von Aquitanien - Foerster, Anne (Eroberte im Mittelalter: Umbruchssituationen erleben, bewältigen, gestalten)

Charles Perraults 'Le Siècle de Louis le Grand' oder die Erfindung von Traditionen - Steigerwald, Jörn (Zeiten bezeichnen. Frühneuzeitliche Epochenbegriffe: europäische Geschichte und globale Gegenwart)

Efficient gradient enhancements for plasticity with ductile damage in the logarithmic strain space - Friedlein, Johannes; Mergheim, Julia; Steinmann, Paul (European Journal of Mechanics - A/Solids)
We contrast different gradient-enhancements for plasticity-damage material models in the logarithmic strain space and compare them to reference models based on multiplicative plasticity. The models being compared include plasticity - gradient-damage, where the gradient-enhancement is applied on the local damage variable, and gradient-plasticity - damage with a gradient-enhanced plastic hardening variable. Thereby, gradient-plasticity proved to be able to simultaneously regularise plastic and ductile (plasticity-driven) damage localisation as confirmed by numerical localisation analyses. This appears to be especially advantageous for logarithmic strain space plasticity-damage, because of the observed plastic localisation even for the case of plasticity with hardening. Even though gradient-plasticity appears to be numerically more demanding, two numerical examples indicate a good robustness and mesh objectivity in the softening regime. Moreover, the internal length for plasticity is able to adjust the damage zone width, similarly to gradient-damage, however ensuring a priori that damage takes place exclusively inside the plastic zone.
Keywords: Finite plasticity; Logarithmic strain space; Ductile damage; Gradient-enhancement; Gradient-plasticity; Gradient-damage; Loss of ellipticity

LoRa Transceiver for Load Monitoring and Control System in Microgrids - Mwammenywa, Ibrahim; Petrov, Dmitry; Holle, Philipp; Hilleringmann, Ulrich (2022 International Conference on Engineering and Emerging Technologies (ICEET))

Polarization dynamics in spin‐VCSELs with integrated surface grating for high birefringence splitting - Lindemann, Markus; Jung, Natalie; Gerhardt, Nils Christopher; Hofmann, Martin R.; Manrique‐Nieto, Nicolas; Pusch, Tobias; Michalzik, Rainer (Electronics letters)

Coupled Aperture VCSELs Suitable for 100 GHz Intensity Modulation - Lindemann, Markus; Gerhardt, Nils C.; Hofmann, Martin R.; Ledentsov, N.; Shchukin, V. A.; Ledentsov, N. N.; Makarov, O. Yu.; Chorchos, L.; Turkiewicz, J. P. (2023 23rd International Conference on Transparent Optical Networks (ICTON))

Analysing the API learning process through the use of eye tracking - Sparmann, Sören; Schulte, Carsten (2023 Symposium on Eye Tracking Research and Applications)